Incidence and risk of herpes zoster in patients with ulcerative colitis and Crohn's disease in the USA. (12th April 2023) - Singer, David; Thompson-Leduc, Philippe; Gupta, Deepshekhar; Cheng, Wendy Y; Poston, Sara; Ma, Siyu; Pawlowski, John E; Duh, Mei Sheng; Morris, Eric D; Devine, Francesca; Farraye, Francis A
Abstract: Background: Patients with inflammatory bowel disease (IBD) are at increased risk of herpes zoster (HZ). We evaluated the incidence of HZ in ulcerative colitis (UC) and Crohn's disease (CD) patients and compared this with HZ incidence in a non-IBD population. Methods: We conducted a retrospective cohort study (GSK study identifier: VEO-000043) of adults aged ≥18 years with UC and CD and without IBD who were identified from claims recorded in a US healthcare database between October 2015 and February 2020. Crude HZ incidence rates/1, 000 person-years (PY) were calculated, and comparisons of HZ incidence rates between UC or CD and non-IBD cohorts were made using adjusted generalized linear models. Results: The study population comprised a total of 29, 928 UC, 25, 959 CD, and 11, 839, 329 non-IBD patients. Crude overall HZ incidence rates were 13.64/1, 000 PY (UC), 15.94/1, 000 PY (CD), and 7.95/1, 000 PY (non-IBD). UC and CD patients had increased HZ incidence rates, with adjusted incidence rate ratios of 1.35 (95% confidence interval [CI], 1.26–1.44) and 1.66 (95% CI, 1.56–1.77), respectively, compared with non-IBD patients. Stratified analysis indicated increased relative rates of HZ in progressively younger age strata in the UC and CD patients compared with non-IBD patients. HZ incidence rates were higher in UC and CD patients who had previously received thiopurines or methotrexate, TNF-inhibitors, or corticosteroids than in UC and CD patients who did not take those medicines. Conclusion: UC and CD patients had increased HZ incidence rates compared with patients without IBD, demonstrating the importance of HZ prevention in IBD patients. Graphical Abstract: